Ambiguity in Corporate Duty of Care relating to Delictual Liability - Segarajasingham, Shanthi (University of Colombo, 2011)
It is well-known that companies are legal persons having separate identity, distinct and independent from its shareholders. This gives the company the right to sue when tort is committed against it. On the other hand, when employees commit tort due to their negligence the company will be liable when such an act is within the scope of employment. Law relating to vicarious liability, even when the employer is a company, is almost settled. In applying this principle of tort to company law, a company will not be considered as vicariously liable but will be liable as the company and this liability is regarded as direct rather than derivative. In such cases it was never a question whether the company owed a duty of care to the injured; instead, it was the employee who owed a duty of care. At the same time, the company is liable for the torts committed by its directors or managers on the application of the principle of agency when such agents act within the actual or apparent authority. Further, in the context of company law, when directors or managers act negligently, the natural person committing the act is identified with the company, and as such, the actions and thoughts of that person are attributed to be those of the company itself. This is called the doctrine of alter ego. While the legal personality concept is very strong and it is well accepted that a company is separate from its shareholders, this contra concept too is 158 DFFHSWHGLQ VRPH FDVHV VD\LQJWKDWWKH GLUHFWRU PDQDJHU DUHWKH µGLUHFWLQJPLQG¶ RIWKH company, despite the fact that the courts are unable to come to a uniform principle as to ZKDWUDQNLQWKHFRPSDQ\¶VKLHUDUFK\ZLOOEHFRQVLGHUHGDVWKHalter ego. While there are sufficient authorities for the acceptance of this concept of alter ego, it has been also decided that a director will not be liable in tort if he does no more than carrying out his constitutional function in governing the company by voting at board meetings, as in MCA Records v. Charly Records.( [2001]. The above two situations bring in a position that when an employee commits a tort the company becomes liable by applying the concept of vicarious liability, and when a tort is committed by a director, the company may become liable if that director has been a directing mind or a force behind such commission. These are by accepting the fact that companies have no physical existence and have to act through human agents. In that case, the question is how is the mental element necessary for any delictual action is measured when a company is responsible? This question brings in the concepts of tort law into the sphere of company law. Under English Law, major part of tort law is based on the notion of negligence which is dependent on the question whether the respondent owed the required duty of care. Negligence is the state of mind and the liability for tort is based on the basis of fault or intention to cause harm. The concept of duty of care under English Law has in modern times become an arcane mystery, comments exponents. The courts consider the question of duty only as a question of law and in most cases the duty of care is connected to notions such as reasonableness, foreseeability, neighbor principle, proximity etc in order to establish the negligence and to estimate the resultant loss. Likewise, under the Roman Dutch Law the fault element for liability under Aquilian Action is either dolus (intention) or culpa (negligence). Here the test for determining dolus is said to be subjective and so relates to the state of mind of the defendant including knowledge of unlawfulness. These basic laws indicate that mental element is important for delictual liability. Nevertheless, there has been no authority how this is measured when a company is a defendant in a tort action. This had not been an issue few decades ago. The position changed in the last two/three decades of the 20th century during which period there had been diversified and complex nature of incidents involving duty of care of companies. For example, as in the cases of Winnipeg Condominium Corporation No. 36 v. Bird Construction Co. (1995) the question 159 was whether a construction company involved in building can be responsible to tenants or occupiers of the building for many years in the future. It was held that the law has now progressed to the point where contractors (as well as subcontractors, architects and engineers) who take part in the design and construction of a building will owe a duty in tort to subsequent purchasers of the building (who is not in contractual privity with the contractor) if it can be shown that it was foreseeable that a failure to take reasonable care in constructing the building would create defects that pose a substantial danger to the health and safety of the occupants. Further, a manufacturing company will be caught up for product liability for defective products as in the case of Grimshaw, v. Ford Motor Company (1981) in which case Ford Pinto manufactured by the defendant company was prone to catching on fire when it hit from the rear due to its design and the defendant company. Though extensive damages were awarded to the plaintiff, it was not on the basis of establishing the duty of care of Ford Company Another peril that is of much concern is health hazards relating to the use of asbestos manufactured by multinational companies. Only in the US the longest and most expensive litigation in tort is said to be pertaining to asbestos related diseases involving more than 8,400 defendants and 730,000 claimants costing over $250 billion by 2006. Furthermore, recent oil spills in oceans due to accidents or ships running aground caused heavy damages. Moreover, the repercussion relating to Bhopal gas leak is still a burning issue against Union Carbide Group since the Indian court has failed to establish the duty of care by the company. Hence, it is high time for courts to determine, in clear terms, the duty of care of companies and the legislature to go for a statute. Is anything similar to Corporate Manslaughter and Corporate Homicide Act 2007 of the UK suitable for other countries, specially Sri Lanka?, is the research question. This is because all developed countries now prefer statutory features rather than common law features. Moreover, statutory provisions embracing case law in the area of tort law will be a new phinominon. Limitation: The presenter seeks to research the duty of care of corporation in different situations and the research does not involve a study based on duty of care of company directors.